Implementasi Pengembangan Agama dan Moral Anak Berdasarkan Teori Lawrence Kohlberg dan Jean Piaget pada Kegiatan Manasik Haji - Rejeki, Ayu Srik; Rani, Indri Mustika; Nazla, Nazla; Nurhayati, Nurhayati; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Religious and moral development in early childhood is an important component in character formation from an early age. To understand how children develop an understanding of values, rules, and moral behavior, Lawrence Kohlberg's theory of moral development and Jean Piaget's theory of cognitive development serve as foundations. Based on these two theories, this study examines the implementation of Hajj rituals as a way to encourage the religious and moral development of early childhood children. Various literature on moral development, early childhood education, and the implementation of Hajj rituals in early childhood education institutions is discussed in this study. The results show that through concrete experiences, habituation, and a clear rule structure, Hajj rituals can foster children's moral development, especially at the heteronomous morality stage (Piaget) and preconventional morality stage (Kohlberg). However, the success of the activities depends heavily on the teacher's ability to incorporate moral principles into each phase of the rituals and provide explanations appropriate to the child's developmental level. This article finds that Hajj rituals have the potential to serve as an effective tool for moral development if conducted in a manner that focuses on the meaning of religious values ​​rather than simply introducing rituals.